(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The current research aims to test the impact of quality of work life in its dimensions (Safety and health in working conditions, Labor Regulations and Laws, Fair and adequate compensation, Career opportunities and job security, Social relevance of work life) on organizational prosperity in its dimensions (organizational capabilities, organizational commitment, leadership support, empowerment) in the Anbar Health Department, In addition to diagnosing the department’s level of interest in the research variables and their sub-dimensions, to come up with a set of recommendations that contribute to improving its practice and adoption of these variables, and based on the novelty of the variables and their urgent importance to the department and its members on the one hand, and society on the other hand, the research adopted the descriptive analytical exploratory approach in its completion. The research adopted the descriptive, analytical, exploratory approach in its completion, as the research community consisted of (97) department leaders, and the questionnaire was distributed to them, for the researcher to retrieve (94), the valid ones were for statistical analysis (92), which is the research sample, The questionnaire was supplemented with data, observations and limited interviews, while the research used statistical programs (SMART PLS V.3.3, SPSS V.28), to analyze the primary data, with the adoption of descriptive and inferential statistics methods, The statistical analysis showed a number of results, the most prominent of which was the adoption by the Anbar Health Department of the quality of work life as a main administrative axis to improve its ability to organizational prosperity through (safety and health of working conditions, Career opportunities and job security, Social relevance of work life).